Avaliação da resistência à corrosão e citotoxicidade de ligas Ti-35Nb-xTa submetidas à tratamentos de superfície - Lima, Thamyres Moura (2018)
Titanium and its alloys are considered to be the most attractive metallic materials for implants because of their excellent mechanical properties, superior biocompatibility and better corrosion resistance in comparison with conventional alloys. Corrosion resistance is a crucial property for this kind of application once physiological fluids are chloride containing solutions. Moreover, their biocompatibility is directly associated with this property. As a result, surface modifications are being utilized on implant surfaces to guarantee an optimal performance. Therefore, in this work, Ti–35Nb–xTa (x = 0; 2.5; 5.0; 7.5) (% wt) alloys were solution treated at 1000◦C /1h and cooled under water, anodized at 20 V for 1 h, and then submitted to electrochemical and cytotoxicity tests, with the intention to evaluate their corrosion resistance and biocompatibility. These tests were also realized in alloys without surface modifications. Outcomes show that the alloys containing bigger amounts of Ta present higher corrosion resistance in SBF. In the anodized alloys, it is also observed an increasing trend when Ta is added to Ti–35Nb alloys. Their higher values of resistance to polarization, Rp, indicate that the formed anodic oxide films provide a better protecting barrier against aggressive ions. In cytotoxicity experiments, the analysis of the data shows that none of the tested samples was cytotoxic after one day of contact with the cells. Comparisons between groups show that there were no statistical differences, except for the Ti-35Nb-7.5Ta alloy without surface modification.